Overview Of The Main Bacterial Infections In Humans - Pieniążek, Jakub Maciej; Padkowska, Aleksandra; Dobosz, Mateusz; Arciszewska, Klaudia; Buczkowski, Jakub; Miazga, Małgorzata; Paprocki, Michał; Mataczyńska, Anna (Quality in Sport, 2024)
Bacterial infections are one of the main challenges of modern medicine, affecting millions of people every year. The ubiquitous microorganisms, such as bacteria, cause many various diseases that can be asymptomatic or mild as well as life-threatening. The purpose of the research is to gain insight into contemporary knowledge about pathogenic bacteria causing the most common diseases in human beings: Gram-Positive Cocci, including S. aureus, S. epidermidis, S. pyogenes, S. agalactiae, E. faecalis, S. pneumoniae, Gram-Negative Cocci, such as N. gonorrhoeae, N. meningitidis, Gram-Negative Bacilli (Enterobacteriaceae), like E. coli, Salmonella, Shigella, K. pneumoniae as well as bacteria of the genus Clostridioides, Pseudomonas, Acinetobacter i Mycobacteria. Information searches were carried out in online databases, scientific, and educational editions, including PubMed, Elsevier, Research Gate, Web of Science, Springer. Bacterial infections are still a huge concern in the modern world. It is necessary not only to constantly update knowledge but also to carry out researces to improve the effectiveness of treatment and prevention against these pathogens.